Who Founds? An Analysis of University and Corporate Startup Entrepreneurs Based on Danish Register Data - Ulrich Kaiser; Johan Moritz Kuhn (Institute of Labor Economics (IZA), 2019)
We compare individuals presently employed either at an university or at a firm from a R&D intensive sector and analyze which of their personal-specific and employer-specific characteristics determine their choice of subsequently founding a startup. Our data set is unusually rich and combines the population of Danish employees with their present employers. We focus on persons who at least hold a Bachelor's degree in engineering, sciences and health and track them over the time period 2001-2012. We show that (i) there are overall little differences between the characteristics of university and corporate startup entrepreneurs, (ii) common factors triggering startup activity of both university and corporate employees are education, top management team membership, previous job mobility and being male, (iii) it is exclusively human capital-related characteristics that affect startup choice of university employees while (iv) the characteristics of the present workplace constitute major factors of entrepreneurial activity.
Keywords: L26; I23; O31; O32; 330; university startups; corporate startups; founder characteristics